Pengaruh Store Atmosphere dan Product Quality terhadap Kepuasan Pelanggan Kopi Sulfan Jakarta Pusat - Reska Neta Febriyana; Fazhar Sumantri; Theysa Sahlani Pratiwi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of store atmosphere and product quality on customer satisfaction at Kopi Sulfan Central Jakarta. The research method used a quantitative approach with non-probability sampling technique through accidental sampling of 100 respondents. Data was collected using a questionnaire with a 5-point Likert scale and analyzed using multiple linear regression with SPSS version 27. The results showed that store atmosphere has a positive and significant effect on customer satisfaction (t count 4.408 > t table 1.984; sig. <0.001). Product quality also has a positive and significant effect on customer satisfaction (t count 7.108 > t table 1.984; sig. <0.001). Simultaneously, both variables have a significant effect on customer satisfaction (F count 203.200 > F table 3.090; sig. <0.01). The coefficient of determination shows that store atmosphere and product quality can explain 80.7% of the variation in customer satisfaction. This study concludes that coffeeshop management needs to pay attention to both aspects simultaneously to create optimal customer satisfaction.